Scholars' attitudes towards the narration of Al-Hassan Al-Basri (may God have mercy on him) On the authority of Imam Ali bin Abi Talib, peace be upon him (Journal of the College of Basic Education, 2023)
Praise be to God, and prayers and peace be upon the Messenger of God, our master Muhammad, and his family and companions.As for after... The Prophet's hadith has a prominent role in preserving the Islamic religion.People to defend this religion by preserving the Book of God and the Sunnah of the Messenger of God (PBUH) and repelling doubts about the Sunnah of His Prophet(PBUH) And there are a number of imams whose condition is well known and their affairs are well known, and the scholars mentioned that they do not narrateto one of them except out of trust, for it was among the blessings of God Almighty upon us if we were of